Aspects and Criticalities of the Fruition in Subjective of the Digital Space: the ‘First Person View’ (diségno, 2021)
The research illustrated here stems from a critical reflection on the theme of ‘first person view’, as defined in the context of interactive virtual digital three-dimensional representations. A reflection arising from the perceptive, communicative, illusory and narrative wonder typical of seventeenth-century architectural perspectives, in contrast with the more slender –compared to the forces at play– suggestive efficacy of the typical scenarios of today’s digital immersive perspective enjoyment. Through an analytical phase of observation of the natural experience of seeing and moving in the space of the real world, an attempt was made to identify some macroscopic critical issues and functional gaps, now deliberately or individually neglected in the implementation of the use of digitally simulated three-dimensional space. In this way, three macro areas of potential intervention have been identified and described in their salient features and, for each of them, some emerging qualitative factors have been focused, the care of which can perfect the experience of three-dimensional fruition and, consequently, the cognitive activity of the digital virtual space, as well as of the information contained therein. The final goal of the research is in fact to perfect and personalize the virtual fruition of digital museum spaces.
Keywords: first person view; perspective; perception; real-time 3D; virtual museums